2017
DOI: 10.5021/ad.2017.29.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Dermoscopy in the Differential Diagnosis of Ruptured and Unruptured Epidermal Cysts

Abstract: BackgroundAn epidermal cyst is a common keratin-filled epithelial-lined cyst. The treatment of choice for epidermal cysts is surgical excision. If the cyst becomes ruptured, incision and drainage with oral antibiotic therapy or intralesional steroid injection are required.ObjectiveTo analyze the dermoscopic features that can differentiate between ruptured and unruptured epidermal cysts.MethodsThe clinical and dermoscopic features of the pathologically confirmed epidermal cysts of two subgroups of 38 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
2
19
0
1
Order By: Relevance
“…Given the limitations of retrospective series evaluation, our study has confirmed the importance of using high frequency probes in evaluating skin lesions also for sebaceous cysts, for better characterization and, consequently, better differential diagnosis, which is fundamental in patients with multiple and concurrent dermatological diseases in everyday clinical practice . In our experience with higher frequency probes and in more significant case series, the morphostructural characteristics described in the literature for the diagnosis of so‐called sebaceous cysts were confirmed, but moreover it showed the high incidence and diagnostic significance of so‐called skin pores, which is a usual finding of these lesions and therefore extremely significant for the differential diagnosis of this disease …”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…Given the limitations of retrospective series evaluation, our study has confirmed the importance of using high frequency probes in evaluating skin lesions also for sebaceous cysts, for better characterization and, consequently, better differential diagnosis, which is fundamental in patients with multiple and concurrent dermatological diseases in everyday clinical practice . In our experience with higher frequency probes and in more significant case series, the morphostructural characteristics described in the literature for the diagnosis of so‐called sebaceous cysts were confirmed, but moreover it showed the high incidence and diagnostic significance of so‐called skin pores, which is a usual finding of these lesions and therefore extremely significant for the differential diagnosis of this disease …”
Section: Resultssupporting
confidence: 71%
“…Depending on their location, we often use probes with different frequencies for the same lesion in order to gain an optimal visualization of both deep and the more superficial structures. In particular, high frequency probes for sebaceous cysts provide the ability to better characterize the more superficial structures, such as skin pores, which are outpouchings that extend from the cyst to the epidermis, an expression of an obstructed piliferous follicle from which the disease originates, thus making up its peculiar characteristic . In fact, from our experience, cysts in 97 out of 118 cases are almost always visible.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations